Campania university students’ motivations to migrate - Santelli, Francesco (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2019)
The students’ mobility is one specific category of the most general phenomenon called “intellectual migration”, originally called “brain drain”, whose debate dates back to the 1960s, when a quantitatively significant number of qualified people began to emigrate from less wealthy countries towards the richer and more advanced ones. The paper analyses the Italian internal migration flows of university students, with a focus on students moving from Campania to the rest of Italy to complete their higher education. With the aim to determine these motivations of such mobility, we use multilevel models to analyze and investigate the key reasons that push university students’ to migrate. We define four macro-determinants: 1) forced-type migration 2) anticipatory migration, 3) prestige migration 4) mobility due to closeness The empirical analysis is divided into two sections. First one is exploratory analysis, while in the 2nd part multilevel model is performed in an ecological approach, with universities acting as elementary units, and regions as units of upper level. It exploits the natural hierarchical structures of data, with universities nested in regions. Response variable is total number of university students’ from Campania enrolling in other regions. The aim is to test and discuss explanatory variables linked to the 4 working hypotheses, with respect to the school-university transition. Model findings are will give an hint about real motivations, confirming or disconfirming determinants related to the each of the 4 working hypothesis.